The Use of Eucalyptus Barks for the Adsorption of Heavy Metal Ions and Dyes - R. Saliba; H. Gauthier; R. Gauthier; M. Petit-Ramel (Adsorption Science & Technology)
Eucalyptus barks harvested in Lebanon were used for the adsorption of pollutants such as heavy metal ions and dyes. Washing with water or pretreatment with formaldehyde was performed on the bark powder. The adsorption capacity of this material towards Cu II , Cr III , Cd II and Ni II was evaluated in a batch process for various parameters. The results obtained showed that the retention capacity increased with contact time, pH and initial metal ion concentration but decreased with temperature. The adsorption capacities were 2.61, 0.71, 2.24 and 0.75 mmol/g adsorbent for Cu II , Cr III , Cd II and Ni II , respectively. Eucalyptus barks are also very efficient for the adsorption of dyes (Acid Blue 25, Erichrome Blue Black B and Calmagite) because of interaction between the hydroxy and amino groups of the dyes and the phenolic moities of bark. This adsorption was modified when metal ions had already been adsorbed on to the barks as a result of the formation of a 1:1 complex between the dye and the metal ion. Desorption was achieved by treating with the sodium salt of ethylenediamine-tetraacetic acid (EDTA) for metal ions and by heating at 75°C in aqueous medium for dyes. After desorption, the recycling of the support was tested for potential use as a means of concentrating pollutants.